Metaphor, making and mysticism: radical re-imagining in language and art - Gallagher, Sheila; Nelstrop, Louise; Shahan, Lydia (Contemporary theological explorations in mysticism, 2026)
"This volume focuses on the interplay between metaphor, making and mysticism and sheds new light on the power of the metaphorical and creative dimensions of the mystical for the twenty-first century. It explores the ways a variety of mystical writers deal with metaphor and image by bringing together chapters from interdisciplinary vantage points - theological, philosophical, historical, artistic, and literary. The book touches on a range of historical and contemporary figures, including Jalal al-Din al-Rumi, John of Ruusbroec, Hadewijch, John Scottus Eriugena and Edward Abbey. In reviewing the place of metaphor in mystical texts (both Christian and Islamic) the contributions reflect on the hard and difficult places both metaphor and mysticism can bring us to. They explore contemporary artists' engagement with the mystical, and how these open up new ways of reimagining our present - moving us beyond static categories such as religion vs. secular, and Christianity vs. Islam. Overall, the book highlights the potential of mysticism to push us beyond comfortable spaces and associations, and considers the language and images used to do so"-- Provided by publisher